Expression of Vacuolar H+-ATPases and the intracellular pH values in three adenocarcinoma cell lines of digestive system - Zou, X-P.; Chen, M.; Zhang, X-Q.; Zhang, B.; Cao, J.; Luo, H-S. (Cellular and Molecular Biology, 2010)
Vacuolar H+-ATPases function in bone resorption, pH homeostasis and tumor metastasis, play an important role in regulating the extra- and intracellular pH (pHe and pHi) in various eukaryotic cells. Acidity is one of the main features of the tumors. The Vacuolar H+-ATPases are the primary responsible for the control of tumor microenvironment by proton extrusion to the extracellular medium, which play a crucial role in tumor invasion, metastasis and chemoresistance. Therefore our study aimed to uncover the relationship between Vacuolar H+-ATPases and the pHi value. Three adenocarcinoma cell lines of digestive system including SGC7901, HT29 and PATU8988 were cultured in RPMI-1640 supplemented with 10% fetal bovine serum and antibiotics. BCECF-AM pH-sensitive fluorescent probe was used to measure the pHi value of cells. Western blot and immunofluorescent staining were respectively applied to determine the protein expression and intracellular distribution of Vacuolar H+-ATPases. The pHi value of HT29 was the highest, whereas the pHi value of PATU8988 was the lowest and of SGC7901 was in the midst according to fluorescent intensity of BCECF. Similar results were obtained in the protein expression and the IOD (integral optical density) of Vacuolar H+-ATPases in them. The pHi value indirectly represented by fluorescent intensity of BCECF was positively correlated with protein expression of Vacuolar H+-ATPases in an exponential manner.